The parallel‐stranded d(CGA) duplex is a highly predictable structural motif with two conformationally distinct strands. Issue 3 (21st February 2022) - Luteran, Emily M.; Paukstelis, Paul J.
Abstract : The first structural characterization of long tandem repeats of the d(CGA) triplet motif in the parallel‐stranded duplex form is provided and the results show that each strand within the duplex is conformationally distinct and plays a unique role in accommodating duplex asymmetry. The structural uniformity of tandem d(CGA) base‐paired triplets obtained from different solution environments further demonstrates that the d(CGA)‐based parallel‐stranded duplex is a robust and highly predictable structure with applications in DNA nanotechnology. Abstract : DNA can adopt noncanonical structures that have important biological functions while also providing structural diversity for applications in nanotechnology. Here, the crystal structures of two oligonucleotides composed of d(CGA) triplet repeats in the parallel‐stranded duplex form are described. The structure determination of four unique d(CGA)‐based parallel‐stranded duplexes across two crystal structures has allowed the structural parameters of d(CGA) triplets in the parallel‐stranded duplex form to be characterized and established. These results show that d(CGA) units are highly uniform, but that each strand in the duplex is structurally unique and has a distinct role in accommodating structural asymmetries induced by the C–CH + base pair.